2023
DOI: 10.21203/rs.3.rs-3268081/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Process evaluation of a tailored nudge intervention to promote appropriate care and treatment of older patients at the end-of-life

Ella L. Bracci,
Adrian G. Barnett,
Christine Brown
et al.

Abstract: Background Non-beneficial treatment affects a considerable proportion of older people in hospital, and some will choose to decline invasive treatments when they are approaching the end of their life. The Intervention for Appropriate Care and Treatment (InterACT) study was a 12-month stepped wedge randomised controlled trial with an embedded process evaluation in three hospitals in Brisbane, Australia. The aim was to increase appropriate care and treatment decisions for older people at the end-of-life, through … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The process evaluation, which included interviews with clinicians enrolled in the trial, revealed that some clinicians felt able to identify patients near the end of life and questioned the sensitivity of the screening tools; specifically, two medical teams from one hospital found that the at-risk score of two for the SPICT tool was achieved by the vast majority of their patients as they all received one point for an unplanned admission [ 17 ]. The interviews also found ‘death denying’ views amongst some clinicians and a perceived lack of educational preparation in end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The process evaluation, which included interviews with clinicians enrolled in the trial, revealed that some clinicians felt able to identify patients near the end of life and questioned the sensitivity of the screening tools; specifically, two medical teams from one hospital found that the at-risk score of two for the SPICT tool was achieved by the vast majority of their patients as they all received one point for an unplanned admission [ 17 ]. The interviews also found ‘death denying’ views amongst some clinicians and a perceived lack of educational preparation in end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported on secondary outcomes 4, 5 and 6 using data immediately available on trial completion [ 16 ]. The cost-consequence analysis, outcomes 8 and 9, will be published separately, and the process evaluation results (outcome 10) are available [ 17 ]. ICU admission was chosen as the primary outcome due to the increasing number of ICU admissions of older patients [ 18 ] and the potential for highly invasive treatments that unnecessarily increase suffering at the end of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation